Modelling and hardware co-simulation of a Quadrotor unmanned aerial vehicle. (2018) - Bouallègue, Soufiene; Fessi, Rabii
This paper deals with the modelling and hardware (HW) co-simulation of a Quadrotor vertical take-off and landing (VTOL) type of unmanned aerial vehicle (UAV). The developed HW co-simulation platform is based on a reconfigurable I/O (RIO) board of National Instruments (NI) Company, called sbRIO-9636, and a host PC with a real-time operating system (RTOS). The control design and simulation (CDSim) module of LabVIEW environment as well as an established network streams data communication protocol are used to emulate and co-simulate all flight dynamics' within a processor-in-the-loop (PIL) framework. The flight motion principle of the Quadrotor, i.e. lift, rotation and translation, is firstly described as function of changes in the angular speed of the rotors. All aerodynamic forces and moments of such a vehicle are then described within an inertial earth frame and a nonlinear dynamical model is established thanks to the Newton-Euler formalism. The dynamics of the propellers' brushless DC motors, accelerometer and gyroscope types of sensors are also modelled and co-simulated in order to complete the established model of the studied VTOL rotorcraft. HW simulations are carried out and compared to those obtained with software (SW) simulations in order to show the effectiveness of the proposed PIL co-simulation strategy.